lmplementasi Analisa Jabatan dalam Menata Organisasi Birokrasi yang Efektif di Daerah (Studi Kasus pada BKD Kota Mataram) - Safitri, Yudiantarti; Indraswari, Harida (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2010)
Bureaucratic reforms are necessary in order to improve local governments’s effectiveness. The necessary bureaucratic reforms are: 1) organizational restructuring, 2) bussiness process improvement, 3) human resource management increase, and 4) remuneration improvement. Job analysis can accerelate bureaucratic reforms. Job analysis is the processes, method and techniques that again data and information which can be used to improve institutional programs, human resources and management. Data analysis is focused on two main aspects: 1) Suitability between described job functions abd duties, and 2) Formulation of consistent job description duties and rules of writing. The result from the research in BKD Mataram City are that there is inconsistency when formulating main duties and functions with applicable rules of writing; so reforms must be made that result in consistent rules of writing that are understood by all staff members. The main benefit of implementing BKD Mataram City’s recommended actions of reforming and clearly defining duties and functions will be to set up the needed positions within the organizational structure that will lead to an efficient wor environment.